Adoptive cell therapy with macrophage-drug conjugates facilitates cytotoxic drug transfer and immune activation in glioblastoma models - Sun, Miaomiao; Bialasek, Maciej; Mayoux, Maud; Lin, Meng-Syuan; Buck, Alicia; Marszałek, Ilona; Taciak, Bartłomiej; Bühler, Marcel; Górczak, Małgorzata; Kucharzewska, Paulina; Kurpiel, Daria; Siemińska, Małgorzata; et al. (Science translational medicine, 2025)
The treatment of solid tumors faces substantial hurdles because of inadequate drug delivery and the immunosuppressive tumor microenvironment. To address these challenges, we developed a therapeutic platform using macrophages loaded with ferritin-drug conjugates, referred to as macrophage-drug conjugates (MDC), and applied it to glioblastoma, an immunologically cold solid tumor. MDC loaded with ferritin-conjugated monomethyl auristatin E enabled efficient, cell contact-dependent transfer of the payload by a mechanism involving transfer of iron-binding proteins, from either mouse or human macrophages preferentially into glioma cells. This targeted delivery and therapeutic efficacy was demonstrated across in vitro coculture systems, ex vivo assays using dissociated glioblastoma patient tumor samples, and in vivo using orthotopic glioblastoma mouse models, all while maintaining a favorable preclinical safety profile evidenced by minimal systemic toxicity and localized drug biodistribution. Beyond direct tumor cell killing leading to significant tumor regression and prolonged survival in these models, MDC therapy reprogrammed the immunosuppressive tumor microenvironment. Immune profiling by spectral flow cytometry revealed enhanced infiltration and activation of cytotoxic T lymphocytes and B lymphocytes while reducing immunosuppressive regulatory T cells. This culminated in a robust, durable, T cell-dependent antitumor immune response, the necessity of which was confirmed through studies in immunodeficient mouse models and by lymphocyte depletion, and which conferred protection against tumor rechallenge. The combined cytotoxic and immunomodulatory effects highlight the potential of MDC therapy as a promising strategy for glioblastoma treatment and support its further clinical development.